Applying Software Wrapping on Performance Monitoring of Web Services - Yu, Liguo (INFOCOMP Journal of Computer Science, 2007)
Commercial, scientific, and social activities are increasingly becoming dependent on service-based web applications. Web-services are influenced by many uncontrollable factors. It is difficult to predict their performance only based on the pre-deployment testing. The performance characteristics, such as response time and failure rate, are volatile and therefore crucial in web service-based application. This paper states that it is important to continually monitor the performance of web-services during the process of their invocation on the client site. In this study, a wrapping-based approach to monitor the performance of web-services is presented and the results of a preliminary experiment that utilizes this approach are reported.